IDENTIFIKASI INDIKATOR UTAMA PENENTU TABUNGAN DOMESTIK BRUTO DI INDONESIA - Hulu, Dalizanolo (E-Journal Widya Ekonomika, 2018)
Domestic savings rate or Gross Domestic Savings Rate (GDSR) as one of the nation's strengths for development financing. The purpose of this study is to find out the main indicators of GDSR in Indonesia using annual periodic data from 1971 to 2016. Using the OLS (ordinary least squares that satisfy all the classic OLS feasibility assumptions, four economic indicators are found to be the main determinants of GDSR in Indonesia, namely (1) saving habits, (2) inflation, (3) exports, and (4) imports. It can be concluded that Using OLS method but ignoring the classical assumption of OLS eligibility, from 11 independent variables, (a) as many as three non-pithy variables, namely (1) Gini index, (2) money supply (M2), and (3) (2) GDP growth, (3) industrial added value, (4) export, (5) import, (6) age dependency ratio, (7) urban population, and (8) inflation.